Matematică
andreimihalache
2015-11-16 13:05:54
(2x-1)^2-2(x+4)=(2x+1)^2+3(x+2)-1
Răspunsuri la întrebare
Any201084
2015-11-16 19:51:09

Salut, (2x-1)²-2(x+4) = (2x+1)²+3(x+2)-1 4x²-4x+1-2x-8 = 4x²+4x+1+3x+6-1 4x²-6x-7 = 4x²+7x+6 -6x-7x = 6+7 -13x = 13 x = 13/-13 x = -1. Succes! :3

danyela3
2015-11-16 19:52:24

(2x-1)^2-2(x+4)=(2x+1)^2+3(x+2)-1 4x^2 - 4x + 1 - 2x - 8  = 4x^2 +4x + 1 + 3x +6 - 1  4x^2 - 6x - 7 = 4x^2 +7x + 6  4x^2 - 6x - 4x^2 - 7x = 6 +7  - 13x = 13  x = 13 : - 13  x = - 1 

Adăugați un răspuns